The Nineteenth Amendment women's right to vote - Peterson, Judy Monroe (Constitution (Springfield, Union County, N.J.), 1998)
Traces the history of the women's rights movement in the United States which culminated in 1920 with the passage of the constitutional amendment giving women the right to vote.